Experimental Evaluation of Actuation and Sensing Capabilities of a Haptic Device - Mobedi, Emir; Görgülü, İbrahimcan; Dede, Mehmet İsmet Can; Dede, Mehmet İsmet Can; Görgülü, İbrahimcan (Springer, 2019)
Haptic devices are used to increase the telepresence level by providing the sense of touch to the human operator. Simultaneously, they capture the targeted motion of the human operator to generate a motion demand for the teleoperated slave system. Considering a scenario where the slave system’s end-effector is handled by the human operator at the master side, which is attached to the haptic device, an ideal haptic interaction involves the feeling of only the end-effector dynamics and the accurate sensation of the end-effector pose. The performance of a haptic device is based on these two functionalities. In this paper, the experimental evaluation of the actuation and sensing capabilities of a haptic device, HIPHAD v1.0 kinesthetic haptic device, is presented.
Keywords: Haptic interfaces; Experimental performance evaluation; System identification; Haptic devices